Apraxia of speech and cerebellar mutism syndrome: a case report. Issue 1 (December 2017) - De Witte, E.; Wilssens, I.; De Surgeloose, D.; Dua, G.; Moens, M.; Verhoeven, J.; Manto, M.; Mariën, P.
Abstract Background Cerebellar mutism syndrome (CMS) or posterior fossa syndrome (PFS) consists of a constellation of neuropsychiatric, neuropsychological and neurogenic speech and language deficits. It is most commonly observed in children after posterior fossa tumor surgery. The most prominent feature of CMS is mutism, which generally starts after a few days after the operation, has a limited duration and is typically followed by motor speech deficits. However, the core speech disorder subserving CMS is still unclear. Case presentation This study investigates the speech and language symptoms following posterior fossa medulloblastoma surgery in a 12-year-old right-handed boy. An extensive battery of formal speech (DIAS = Diagnostic Instrument Apraxia of Speech) and language tests were administered during a follow-up of 6 weeks after surgery. Although the neurological and neuropsychological (affective, cognitive) symptoms of this patient are consistent with Schmahmann's syndrome, the speech and language symptoms were markedly different from what is typically described in the literature. In-depth analyses of speech production revealed features consistent with a diagnosis of apraxia of speech (AoS) while ataxic dysarthria was completely absent. In addition, language assessments showed genuine aphasic deficits as reflected by distorted language production and perception, wordfinding difficulties, grammatical disturbances and verbal fluency deficits. Conclusion To the best of our knowledge this case might be the first example that clearly demonstrates that a higher level motor planning disorder (apraxia) may be the origin of disrupted speech in CMS. In addition, identification of non-motor linguistic disturbances during follow-up add to the view that the cerebellum not only plays a crucial role in the planning and execution of speech but also in linguistic processing. Whether the cerebellum has a direct or indirect role in motor speech planning needs to be further investigated.